Penyembuhan Luka Post Sectio Cesarea (SC) Dengan Ekstrak Ikan Gabus (Channa Striata) - Ummah, Wiqodatul; Ningrum, Novi Budi (Universitas Tribhuwana Tunggadewi, 2022)
The fulfilment of high protein is one of the determinants of wound healing. Snakehead fish (Channa Striata) is a fish that has high protein and albumin. Protein supplies amino acids needed for tissue repair and regeneration, thereby influencing wound healing. The purpose of this study was to analyse the effect of snakehead fish extract on wound healing in post section-caesarean (SC). The research design used a quasi-experimental with a pre-test and post-test control group design. The population was all postpartum with SC, with as many as 30 mothers at Permata Hati Hospital, Malang. The research sample was 30 respondents divided into two groups (intervention and control groups as many as 15 postpartum, respectively). The intervention group receive a daily dose of 1000 mg of the fish extract and antibiotics, while the control group was given antibiotics only for 14 days. Wound status was assessed with the REEDA scale. The data were analyse using univariate and bivariate with an Independent t-test. Results showed there was a significant difference in wound status between groups (p = 0.0010.05). It can be concluded there was a significant effect of Channa Striata extract on post section-caesarean wounds among participants. Snakehead fish has the highest albumin content and support the wound healing process, especially for post-operative patients. Further research on the benefits of snakehead fish extract in increasing haemoglobin levels among post-partum mothers with anaemia is needed.